Pre-Exposure Prophylaxis for Human Immunodeficiency Virus in the Medical Curricula in Portugal: A Cross-Sectional Analysis - Duarte, Francisco (2022)
Introduction: Pre-exposure prophylaxis (PrEP) has gained relevance as a method of prevention for HIV in certain people and settings. Following the publication of the guideline on PrEP prescribing in Portugal, we aimed to assess the knowledge of Portuguese Medical Students about PrEP.Material and Methods: An online survey was sent to Medical students of Portuguese Medical Schools. We conducted a descriptive analysis of the results and an analytic cross-sectional study to identify factors associated with “knowing about PrEP”, “having had one class about PrEP” and “identifying eligible groups correctly”.Results: Of the 796 students that responded to the survey, 64.6% were aware of what PrEP is. Of these, 34.44% acquired this knowledge during their training. Out of the total amount of respondents, 4.77% could identify correctly and completely the eligible groups for PrEP. As the training years went by, the probability of being aware of PrEP, having had one class about PrEP, and identifying the eligible groups correctly, increased. Of the sixth-year students, 43.48% had had one class about PrEP and among the students that were aware of PrEP, 28% identified what the eligible groups were. After adjusting for the school year, we found differences between Medical Schools regarding the outcomes. The association between the different ways of learning about PrEP and the ability to correctly identify eligible groups for PrEP was not statistically significant.Conclusion: The differences between Medical Schools could be harmonized through changes in the medical curricula that would allow this topic to be addressed more often.